Le point de vue du Groupement des assureurs automobiles sur les centres d’estimation - Medza, Raymond (Assurances, 1984)
In this article, Mr. Raymond Medza, managing director of the Groupement des assureurs automobiles, describes the operations of the estimate centres and replies to some of the criticisms made by the Automobile Protection Association. This article is of interest as it shows how the G.A.A. has set-up its estimate centres in Quebec and what results have been obtained.